PENGARUH PENGGUNAAN ENDORSEMENT TERHADAPMINAT BELI KONSUMEN PADA AISYKOTA BIMA - Mizwar Mizwar; Muhajirin Muhajirin (Jurnal Ilmiah Satyagraha, 2021)
Satisfying consumer needs is the desire of every company. Apart from beingan important factor for the survival of the company, satisfying consumer needs canincrease its superiority in the competition. Consumers who are satisfied withproducts and services tend to repurchase the product and reuse the service when thesame need reappears in the future. This study aims to determine the effect of the useof endorsements on consumer buying interest at AISY Bima city. This study uses aquantitative approach with a survey method. The population in this study areconsumers who have seen endorsements that promote AISY products, the number ofsamples taken in this study were 50 respondents with the sampling used in this studywas purposive sampling. The research instrument used a questionnaire with a Likertscale. Data analysis used simple linear regression, partial test with t test. To test theeffect between variables using SPSS (Statistical Service Product Solutions) version23.00. The results showed that endorsement had a positive and significant effect onbuying interest at AISY in Bima city.